Satuan Lingual dalam Aktivitas Pemanfaatan Sungai Mbah Tonjong di Dusun Kedung Glatik, Desa Candirejo, Kec. Pringapus, Kab. Semarang (Jurnal Sosial Humaniora dan Pendidikan, 2025)
This study aims to describe the lingual units used in the utilization activities of Mbah Tonjong River by the people of Kedung Glatik Hamlet, as well as to examine the relationship between language and local culture reflected in the use of these lingual units. The approach used is qualitative with the method of language ethnography, where data is collected through participatory observation, in-depth interviews, and documentation. The analysis was conducted using the Sapir-Whorf ethnolinguistic theory which emphasizes that language shapes people's perspective and socio-cultural reality. The results show that lingual units in activity expressions such as adus kali, jeguran, kungkum, as well as ritual terms such as nazar and munjung not only function as naming activities, but also reflect cultural values, belief systems, and meaning constructions that live in the community. Thus, language in this context becomes an important medium in maintaining cultural identity while representing the community's relationship with their natural and spiritual environment. This research contributes to the development of ethnolinguistic studies and the preservation of local languages and cultures.